Resistant starches and gut microbiota. (1st September 2022) - Wen, Jia-Jia; Li, Ming-Zhi; Hu, Jie-Lun; Tan, Hui-Zi; Nie, Shao-Ping
Highlights: The beneficial impacts of resistant starches were summarized. Resistant starches exhibit positive effects on health functions in the host through the enrichment of beneficial gut microbes. Different resistant starches with various fine structures and properties are consumed in different degrees by gut microbiota. The investigation in potential mechanisms of resistant starches-gut microbiota promote the development of functional foods for gut health. Abstract: Resistant starches (RS), which are considered as one of the dietary fibers, could exert widely beneficial impacts, reduce fat accumulation, show significant effects on regulating blood glucose metabolism and insulin levels, and have protective effects on the gut. Five types of RS have different responses to chronic disease by modulating gut microbiota. Short-chain fatty acids are the linkage between gut microbiota and RS, and RS could improve the metabolism of gut microbiota as well as increase the abundance of beneficial microbes in the gut. The composition of gut microbiota is associated with RS properties, which is reflected by the changes of butyrate-producing bacteria primarily influenced by consumption of RS with various fine structures and types of crystallinities. RS with different fine structures and properties is consumed to varying degrees by gut microbiota, which can be applied to produce functional foods for gut health in future.